Gambaran Faktor yang Berhubungan Dengan Kinerja Petugas Dalam Penyediaan Dokumen di RSU Muhammadiyah Ponorogo - Titin Istikomah; Dwi Nurjayanti; Rumpiati Rumpiati (FORUM ILMIAH KESEHATAN, 2019)
It is known that the provision of outpatient medical record documents at Muhammadiyah Hospital Ponorogo is not optimal, because it does not comply with the minimum service standards, namely